2001
DOI: 10.1021/ja015591n
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Control and Reactivity of Pd Complexes with Meso and Racemic Ligands in the Isotactic Alternating Propene−Carbon Monoxide Copolymerization

Abstract: We report here that C 2 -and C s -symmetric [(P∧P)Pd(H 2 O) 2 ](SO 3 -CF 3 ) 2 complexes, P∧P being either a rac-or a meso-diphosphine ligand, catalyze the copolymerization of propene and carbon monoxide to isotactic poly(1-methyl-2-oxo-1,3-propanediyl) (1a); the meso ligands are even more stereoselective than the racemic ligands and display much higher catalytic activity.The relationship between the geometric characteristics of the catalytic system and the microstructure of the produced polymer has received m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The lowest frequency CO absorption from acyl-C(O)Co(CO) 3 L does not noticeably shift during the entire reaction, but its absorbance dwindles somewhat as the polymerization proceeds. Assuming that the molar absorbability is not affected by the chain growth, the above observation Table 2 IR data (hexane, RT) of the CH 3 Co(CO) 3 PR 3 complexes (1) 123.44 (11) 122.06 (12) 122.04(17) 120.6 (3) indicates that the concentration of acyl-C(O)Co(CO) 3 L is the highest at the beginning of the polymerization and decreases somewhat as the polymerization proceeds. A direct comparison of the rate constants was impossible because the order of rate dependence on aziridine concentration appeared to be different when different catalysts were used.…”
Section: The Effect Of Phosphine On the Polymerizationmentioning
confidence: 96%
See 1 more Smart Citation
“…The lowest frequency CO absorption from acyl-C(O)Co(CO) 3 L does not noticeably shift during the entire reaction, but its absorbance dwindles somewhat as the polymerization proceeds. Assuming that the molar absorbability is not affected by the chain growth, the above observation Table 2 IR data (hexane, RT) of the CH 3 Co(CO) 3 PR 3 complexes (1) 123.44 (11) 122.06 (12) 122.04(17) 120.6 (3) indicates that the concentration of acyl-C(O)Co(CO) 3 L is the highest at the beginning of the polymerization and decreases somewhat as the polymerization proceeds. A direct comparison of the rate constants was impossible because the order of rate dependence on aziridine concentration appeared to be different when different catalysts were used.…”
Section: The Effect Of Phosphine On the Polymerizationmentioning
confidence: 96%
“…However, the use of carbonylation in polymer synthesis has primarily been focused on polyketone synthesis [8][9][10][11][12][13][14][15][16][17]. A few early reports and patents in the 1960s disclosed that inorganic compounds of group 8-10 metals, some times in the presence of main group organometallic compounds, catalyzed copolymerizations of CO and oxygen containing comonomers [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that [Pd(PP)(H 2 O) 2 ][OTf] 2 complexes (where PP is either (1R,1'S)-or (1RS,1'RS)-1,2-bis[1,1'-(diphenylphosphino)ethyl]benzene, OTf trifluoromethanesulfonate), when used as catalyst precursors for the copolymerization of propene with CO, produce both isotactic poly(1-methyl-2-oxopropane-1,3-diyl) [8]. The meso-ligand shows higher stereospecificity and much higher catalytic activity than the racemicligand, possibly due to the highly stereo-and regiospecific formation of the olefin intermediate responsible for insertion.…”
mentioning
confidence: 99%
“…4, a) turned out to perform much better than the corresponding racemic derivatives in terms of productivity, regioregularity, and stereoregularity in the CO/propene copolymerization, and give the most isotactic CO/propene ever produced [21]. Finally, the steric and electronic optimization of chiral diphosphinoferrocene ligands of the Josiphos family showed that the electronic effects of the donors boost the productivity of the Pd catalyst in the CO/propene copolymerization, with the electronic asymmetry of the P-donors and the 3,5-disubstitution of one Ar 2 P group playing a pivotal role [22].…”
mentioning
confidence: 96%